A binding cooperativity switch driven by synergistic structural swelling of an osmo-regulatory protein pair - Narayan, Abhishek (Nat Commun, 2019)
Uropathogenic E. coli experience a wide range of osmolarity conditions before and after successful infection. Stress-responsive regulatory proteins in bacteria, particularly proteins of the Hha family and H-NS, a transcription repressor, sense such osmolarity changes and regulate transcription through unknown mechanisms. Here we use an array of experimental probes complemented by molecular simulations to show that Cnu, a member of the Hha protein family, acts as an exquisite molecular sensor of solvent ionic strength. The osmosensory behavior of Cnu involves a fine-tuned modulation of disorder in the fourth helix and the three-dimensional structure in a graded manner. Order-disorder transitions in H-NS act synergistically with molecular swelling of Cnu contributing to a salt-driven switch in binding cooperativity. Thus, sensitivity to ambient conditions can be imprinted at the molecular level by tuning not just the degree of order in the protein conformational ensemble but also through population redistributions of higher-order molecular complexes.